Supplementation with oviductal EVs from the estrus, metestrus, and diestrus stages improved developmental competence of IVF mouse embryos - Yamei Xue; Chao Ling; Haixia Zheng; Kun Li (Scientific Reports)
Abstract Several studies showed that supplementation of oviductal extracellular vesicles (EVs) enhanced the development and quality of the early embryos cultured in vitro. However, our previous study found that the characteristics and the cargos of oviductal EVs varied across the proestrus, estrus, metestrus, and diestrus stages of the mouse estrous cycle. We hypothesized that the addition of EVs from the different stages may have different effects on embryonic development. This study aimed to evaluate the effect of oviductal EVs isolated from the different stages of the mouse estrous cycles on the development of in vitro fertilization (IVF) embryos. Experiment 1 evaluated the effect of oviductal EVs from the proestrus (Pro-EVs), estrus (Est-EVs), metestrus (Met-EVs), and diestrus (Die-EVs) stages on embryonic development. Experiment 2 examined the effect of different addition modes (0–4 EVs, 1–4 EVs, 2–4 EVs, 3–4 EVs and Re-EVs) on embryo development competence. Oviductal EVs were successfully isolated from the four estrous cycle stages, and their characterizations were described. Co-culture of mouse embryos with Est-EVs, Met-EVs and Die-EVs significantly improved the blastocyst yield and hatching rates regardless of supplemental dosages. When the embryos were obtained at 2-cell stage and cultured to the hatched stage, the blastocyst rate significantly increased in the 1–4 EVs, 2–4 EVs and 3–4 EVs groups compared to the control groups. The hatching rate in the 3–4 EVs group was significantly higher than in the other three groups. When 3–8 cells stage embryos were cultured to the hatching stage, the blastocyst and hatching rates significantly increased in the 2–4 EVs and 3–4 EVs groups comparing to the control group, but there were no significant differences between the 2–4 EVs and 3–4 EVs groups. When the embryos at morula stage were cultured, the blastocyst and hatching rates in the 3–4 EVs group were significantly higher than the control group. Die-EVs renewal did not improve the blastocyst formation and hatching rates but significantly increased the blastocyst cell number compared to the 0–4 EVs addition mode. The supplementation with oviductal EVs from the estrus, metestrus, and diestrus stages improved the blastocyst yield and hatching rates of IVF embryos. The different addition modes significantly affected the blastocyst rate of early embryos at the different developmental stages (2-cell, 3–8 cells and morula).